Telaah Literatur Tentang Permintaan Dalam Islam: Integrasi Nilai Syariah Dalam Perilaku Konsumen Muslim - Zafia Sarina Yoly; Mohd Winario; Muhammad Zakir; Zubaidah Assyifa (Journal of Economic, Management, Business, Accounting Sustainability, 2026)
Demand is a fundamental concept in economics that explains the relationship between consumers' needs, desires, and ability to consume goods and services. From an Islamic economic perspective, the concept of demand is not solely based on material satisfaction but is also framed by Sharia values, which emphasize morality, ethics, and social responsibility. This article aims to review the literature related to the concept of demand in Islam and to examine how the integration of Sharia values ​​influences Muslim consumer behavior. The method used is a literature review of various scholarly sources, including books, journals, and articles relevant to Islamic economics and consumer behavior. The results of the review indicate that demand in Islam is influenced by the principles of halal (permissible) and haram (forbidden), balance (wasathiyah), the prohibition of israf (prohibition of excessive consumption), and an orientation toward the benefit of the community. The integration of these values ​​encourages Muslim consumers to be spiritually rational, moderate in consumption, and consider the social and environmental impacts of every economic decision. Thus, the concept of demand in Islam differs from conventional economics because it places Sharia values ​​as the primary foundation in shaping Muslim consumer behavior.